Computed Tomography Evaluation of Esophagogastric Necrosis After Caustic Ingestion. Issue 1 (July 2016) - Chirica, Mircea; Resche-Rigon, Matthieu; Zagdanski, Anne Marie; Bruzzi, Matthieu; Bouda, Damien; Roland, Eric; Sabatier, François; Bouhidel, Fatiha; Bonnet, Francine; Munoz-Bongrand, Nicolas; Marc Gornet, Jean; Sarfati, Emile; et al.
Abstract : Background: Endoscopy is the standard of care for emergency patient evaluation after caustic ingestion. However, the inaccuracy of endoscopy in determining the depth of intramural necrosis may lead to inappropriate decision-making with devastating consequences. Our aim was to evaluate the use of computed tomography (CT) for the emergency diagnostic workup of patients with caustic injuries. Methods: In a prospective study, we used a combined endoscopy–CT decision-making algorithm. The primary outcome was pathology-confirmed digestive necrosis. The respective utility of CT and endoscopy in the decision-making process were compared. Transmural endoscopic necrosis was defined as grade 3b injuries; signs of transmural CT necrosis included absence of postcontrast gastric/ esophageal-wall enhancement, esophageal-wall blurring, and periesophageal-fat blurring. Results: We included 120 patients (59 men, median age 44 years). Emergency surgery was performed in 24 patients (20%) and digestive resection was completed in 16. Three patients (3%) died and 28 patients (23%) experienced complications. Pathology revealed transmural necrosis in 9/11 esophagectomy and 16/16 gastrectomy specimens. Severe oropharyngeal injuries ( P = 0.015), increased levels of blood lactate ( P = 0.007), alanine aminotransferase ( P = 0.027), bilirubin ( P = 0.005), and low platelet counts ( P > 0.0001) were predictive of digestive necrosis. Decision-making relying on CT alone or on a combined CT–endoscopy algorithm was similar and would have spared 19 unnecessary esophagectomies and 16 explorative laparotomies compared with an endoscopy-alone algorithm. Endoscopy did never rectify a wrong CT decision. Conclusions: Emergency decision-making after caustic injuries can rely on CT alone.